Gagasan Muatan Materi dalam Perubahan UUD 1945 - Hasanuddin Hasim (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
Reform 1998 led some party factions and groups to amend the 1945 constitution (amendment). Starting with the first amendment (1999), the second amendment (2000), the third amendment (2001) and the last changes in the fourth (2002). Although it has been four times changed, there are some parts that could not be changed because of the agreement of the founders of the nation at the time of drafting the constitution (BPUPKI) that the 1945 Constitution, the Basic state philosophy of Pancasila, Destination country, Principle of a state of law, principle of popular sovereignty, Principle state unity, and the principle of the republic. In terms of changes to the constitution, there are some things that need to be added to the substance, namely the existence of regulations on the protection of human rights and citizens; The imposition of a state government structure that is fundamental, and their limitations, and the division of tasks is also a fundamental constitutional.